Case report: Undifferentiated sarcoma with multiple tumors involved in Lynch syndrome: Unexpected favorable outcome to sintilimab combined with chemotherapy - Liu, Jiaying; Chang, Xiaona; Xiao, Guixiang; Zhong, Jingmin; Huang, Bo; Zhang, Jiwei; Gao, Beibei; Peng, Gang; Nie, Xiu (Frontiers in Oncology, 2022)
Background: Patients with Lynch syndrome are at an increased risk of developing simultaneous or metachronous tumors, while sarcomas have been occasionally reported. Sarcomas are generally not considered part of the common Lynch syndrome tumor spectrum. However, more and more studies and case reports suggested that sarcoma could be a rare clinical manifestation of Lynch syndrome, leading to new treatment strategies for sarcoma. Case summary: We report the case of a 74-year-old male patient with Lynch syndrome who had rectal mucinous adenocarcinoma and prostate adenocarcinoma and then developed undifferentiated sarcoma of the left neck two years later. Mismatch repair deficiency (dMMR) was confirmed by immunohistochemical staining for the mismatch repair proteins MSH2, MSH6, MLH1 and PMS2. The result of polymerase chain reaction (PCR) microsatellite instability (MSI) testing of sarcoma showed high-level microsatellite instability (MSI-H). Additionally, a pathogenic germline mutation in MSH2 (c.2459-12A>G) was detected by next-generation sequencing (NGS). Taking into account HE morphology, immunohistochemical phenotype, MSI status, NGS result, medical history and germline MSH2 gene mutation, the pathological diagnosis of left neck biopsy tissue was Lynch syndrome related undifferentiated sarcoma with epithelioid morphology. The patient has been receiving immunotherapy (sintilimab) combined with chemotherapy (tegafur, gimeracil and oteracil potassium capsules) and currently has stable disease. We also reviewed the literature to understand the association between sarcoma and Lynch syndrome. Conclusion: Sarcoma may now be considered a rare clinical manifestation of Lynch syndrome. Attention and awareness about the association between Lynch syndrome and sarcoma need to be increased. Therefore, timely detection of MMR proteins and validation at the gene level for suspicious patients are the keys to avoiding missed or delayed diagnosis and to identifying patients suited for immunotherapy, which may also help to provide appropriate genetic counseling and follow-up management for patients.